Commognitive Mahasiswa Dalam Menyelesaikan Soal Kontekstual Pemodelan Matematika - Meilantifa, Meilantifa; Emanuel, Endrayana Putut Laksminto (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This research aims to describe students' cognitive abilities in mathematical modeling material. The methods used in this research are preparation, data collection, transcription and analysis. A total of nine students who were grouped into three groups were given mathematics problem sheets, containing contextual story problems consisting of one number regarding mathematical modeling. A student representing his group was selected as a research subject based on Polya indicators and was interviewed in a semi-structured and in-depth manner to dig up further information and then analyzed cognitively. The research results show that the research subjects can solve mathematical problems well. The subject can communicate ordinary sentences well into mathematical models. The components of words use, visual mediators, narratives, and routines show that students' cognitive ability in solving mathematical contextual problems is very good in mathematical modeling material.